Spatial attention can be biased towards an expected dimension. Issue 11 (November 2016) - Burnett, Katherine E.; Close, Alex C.; d'Avossa, Giovanni; Sapir, Ayelet
A commonly held view in both exogenous and endogenous orienting is that spatial attention is associated with enhanced processing of all stimuli at the attended location. However, we often search for a specific target at a particular location, so an observer should be able to jointly specify the target identity and expected location. Whether attention can bias dimension-specific processes at a particular location is not yet clear. We used a dual task to examine the effects of endogenous spatial cues on the accuracy of perceptual judgments of different dimensions. Participants responded to a motion target and a colour target, presented at the same or different locations. We manipulated a central cue to predict the location of the motion or colour target. While overall performance in the two tasks was comparable, cueing effects were larger for the target whose location was predicted by the cue, implying that when attending a particular location, processing of the likely dimension was preferentially enhanced. Additionally, an asymmetry between the motion and colour tasks was seen; motion was modulated by attention, and colour was not. We conclude that attention has some ability to select a dimension at a particular location, indicating integration of spatial and feature-based attention.